Mediation role of organizational citizenship behavior Work-Life Bal-ance, Job Embeddedness, and Turnover intention in Islamic Banking - Iwan Kresna Setiadi; Dianwicaksih Arieftiara (International Business and Accounting Research Journal, 2022)
This study is to analyze the mediating impact of organizational citizenship behavior, job embeddedness, and work-life balance on turnover intention. Samples were taken from as many as 300 respondents to employees in Islamic banking in DKI Jakarta, Banten, and West Java, Indonesia. The results of the study found that JE and WLB were strongly felt by having a positive effect on IT, as well as JE and WLB on organizational citizenship behavior. An assessment that results in a small OCB but still has an effect on IT. The new findings from this study can explain how OCB mediation is very important for employees who work in Islamic banking, IT has an impact on the continuity of the Islamic banking business during the COVID-19. Therefore, this research can make a big contribution, especially the WLB study can make employees have a good mood at home. Thus, for organizations during the COVID-19 pandemic, employees must feel comfortable and persist in any conditions. A good JE value will have an impact on the sincerity value of employees to work well, this is a positive thing that every organization can implement. Support for employees from the company through an interpersonal relationship approach discussing problems in their family and social life from the impact of COVID 19, is very important, which will strengthen every company organization to continue to run its business in the future.